Does nest site availability limit populations of secondary cavity-nesting birds in Quercus pyrenaica forest?:an experimental approach - Sampaio, Ana Marta Martinho (2009)
Tese de mestrado, Biologia (Biologia da Conservação), 2009, Universidade de Lisboa, Faculdade de Ciências